Pregnancy with successful foetal and maternal outcome in a melanoma patient treated with nivolumab in the first trimester: case report and review of the literature. Issue 3 (June 2019) - Xu, Wen; Moor, Rebecca J.; Walpole, Euan T.; Atkinson, Victoria G.
Abstract : Although T-cell checkpoint blockade has revolutionized melanoma therapy, metastatic melanoma in pregnancy remains a challenging area of unmet need. Treatment with anti-PD1 therapy decreases foetal–maternal tolerance and increases the risk of pregnancy loss in animal studies and is considered category D by the Food and Drug Administration. We describe a unique case of conception and pregnancy, with successful maternal and foetal outcomes, in a patient with metastatic melanoma who had received combination anti-CTLA-4 and anti-PD1 therapy. A 32-year-old G0P0 lady, with a 10-year history of infertility of unclear cause, was found to be 7 weeks pregnant after 14 months of nivolumab maintenance therapy, having previously received combination ipilimumab and nivolumab. Nivolumab was ceased upon discovery of pregnancy in the first trimester. The patient had an uneventful pregnancy, followed by spontaneously premature labour, and delivered by caesarean section at 33 weeks' gestation. The foetus had moderate intrauterine growth restriction, as well as congenital hypothyroidism, which possibly constitutes the first documented case of foetal immune-related adverse event from maternal anti-PD1 exposure. No adverse events were noted in the mother. At 6 months of follow-up postpartum, the mother had a sustained complete response to treatment, and the baby had appropriate weight gain with normal developmental milestones. We summarize and discuss the available literature of immune checkpoint inhibitor exposure in pregnancy, which consists of a total of three case reports.